Percutaneous Nephrolithotomy: Update, Trends, and Future Directions - Ghani, Khurshid R.; Andonian, Sero; Bultitude, Matthew; Desai, Mihir; Giusti, Guido; Okhunov, Zhamshid; Preminger, Glenn M.; de la Rosette, Jean (European urology, 2016)
Percutaneous nephrolithotomy (PCNL) is the surgical standard for treating large or complex renal stones. Since its inception, the technique of PCNL has undergone many modifications. To perform a collaborative review on the latest evidence related to outcomes and innovations in the practice of PCNL since 2000. A literature review was performed using the PubMed database between 2000 and July 2015, restricted to human species, adults, and the English language. The Medline search used a strategy including the following keywords: percutaneous nephrolithotomy, PNL, advances, trends, technique, and the Medical Subject Headings term percutaneous nephrostomy. Population-based studies have now provided a wealth of information regarding patient outcomes following PCNL. The complexity of the stone treated can be quantified using a variety of validated nephrolithometry classification systems. Increasing familiarity with the supine approach to PCNL has enabled simultaneous combined retrograde and antegrade surgery. Advances such as endoscopic guided percutaneous access may help urologists achieve access with less morbidity. Increasing miniaturization of equipment has led to the development of mini, micro, and ultramini techniques. The tubeless method of PCNL is now accepted practice with good evidence of safety in appropriately selected patients. Modern-day PCNL allows personalized stone management tailored to individual patient and surgeon factors. Future studies should continue to refine methods to assess complexity and safety and to determine consensus on the use of miniaturized PCNL. Modern-day percutaneous nephrolithotomy has transformed from an operation traditionally undertaken in one position, using one access method with one set of instrumentation and one surgeon, to one with a variety of options at each step. Popular advances in percutaneous nephrolithotomy over the past decade include nephrolithometry classification systems, supine positioning, endoscopically guided access, simultaneous antegrade and retrograde procedures, new miniaturized instrumentation, and increasing use of a tubeless technique.